Modulating β-catenin/BCL9 interaction with cell-membrane-camouflaged carnosic acid to inhibit Wnt pathway and enhance tumor immune response - Gao, Ruqing; Zheng, Xiaoqiang; Jiang, Aimin; He, Wangxiao; Liu, Tianya (Frontiers in Immunology, 2023)
Introduction: LUAD therapies are plagued by insufficient immune infiltration and suboptimal immune responses in patients, which are closely associated with the hyperactive Wnt/β-catenin pathway. Suppressing this signaling holds considerable promise as a potential tumor therapy for LUAD, but Wnt suppressor development is hindered by concerns regarding toxicity and adverse effects due to insufficient targeting of tumors.We have synthesized a tumor-specific biomimetic Wnt pathway suppressor, namely CM-CA, by encapsulating carnosic acid within LLC cell membranes. It possesses nano-size, allowing for a straightforward preparation process, and exhibits the ability to selectively target the Wnt/β-catenin pathway in lung adenocarcinoma cells. To evaluate its in vivo efficacy, we utilized the LLC Lewis homograft model, and further validated its mechanism of action through immunohistochemistry staining and transcriptome sequencing analyses.The findings from the animal experiments demonstrated that CM-CA effectively suppressed the Wnt/β-catenin signaling pathway and impeded cellular proliferation, leading to notable tumor growth inhibition in a biologically benign manner. Transcriptome sequencing analyses revealed that CM-CA promoted T cell infiltration and bolstered the immune response within tumor tissues.The utilization of CM-CA presents a novel and auspicious approach to achieve tumor suppression and augment the therapeutic response rate in LUAD, while also offering a strategy for the development of Wnt/β-catenin inhibitors with biosafety profile.